(untitled) (Research in Agriculture Livestock and Fisheries, 2023)
An entomological study was conducted at Ishwardi Upazila of Pabna district to identify the species and breeding sites of mosquitoes. Adult mosquitoes were collected using collecting net, human bait, light trap and larvae were collected by ladle spoon, mug, dipper, and pipette from rail junction, bazar, house, cattle shed, rice field, sugarcane field, rice mill, paper mill, drains etc. A total of 2647 mosquito samples including 1426 larvae and 1221 adult mosquitoes were collected from these places. Seven species of larva and eight species of adult mosquitoes under two genera were identified. The recorded genera for both larvae and adults were Culex (Cx.) and Anopheles (An.). The collected species for larvae were Cx. quinquefasciatus, Cx. epidesmus, Cx.tritaeniorhynchus, Cx. mimulus, Cx. sinensis, An. vagus and An. minimus. The collected species for adults were Cx. epidesmus, Cx. quinquefasciatus, Cx.tritaeniorhynchus, Cx. mimulus, Cx. sinensis, Cx. pallidothorax, An. vagus and An. minimus. Among the collected larva, Culex was found most prevalent (85.7%) than Anopheles (14.3%). Same as larva, adult Culex mosquitoes was found most prevalent (84.4%) than Anopheles (15.6%). Cx. quinquefasciatus (33.5%) found highest among the larval prevalence, in contrast, Cx. epidesmus (36.2%) was dominant among adults. On the other hand, An. vagus was the most dominant species in both larval and adult surveillance (8.1% and 9.9%, respectively). Both the larva and adult Culex mosquitoes were found more prevalent in households (20.3% and 41.2%, respectively), whereas density of Anopheles larva was found highest in rice fields (20.6%) and those of adults were concentrated in households (39.5%). The result of this study will help us to develop a sustainable control measures for the mosquitoes and mosquito-borne diseases in the study areas as well as other areas of the country. Res. Agric. Livest. Fish. Vol. 10, No. 2, August 2023: 199-206